Psychology & Christianity : five views - Johnson, Eric L., 1956-; Myers, David G. (Spectrum multiview books., 2010)
This revised edition now presents five models for understanding the relationship between psychology and Christianity. All the essays and responses have been reworked and updated with some new contributors including the addition of a new perspective, the transformative view from John Coe and Todd Hall. Also found here is David Powlison who offers the biblical counseling model. The levels-of-explanation model is advanced by David G. Myers, while Stanton L. Jones offers an entirely new chapter presenting the integration model. The Christian psychology model is put forth by Robert C. Roberts now joined by Paul J. Watson. Each of the contributors responds to the other essayists, noting points of agreement as well as problems they see.--From publisher description.